EKSPLORASI MIXING BINAURAL BEATS PADA BUNYI SULING BAMBU - Dyah Murwaningrum; Satria Mulya; Jaka Gaumantara (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2024)
The binaural beat phenomenon has shown its effectiveness for the world of health, through testing research. Research generally focuses on testing the effectiveness of binaural beats both psychologically and through EEG testing. Meanwhile, binaural therapy music that is circulating for free is formed from digital signal processing using a generator, not real instruments. That is what often affects the willingness and comfort of users. This research is an explorative research with an ethnomusicological approach, especially electroacoustics (digital sound processing technology) and applying the principle of brainwave state. This research is an exploration of binaural beat sound processing using original instruments. This exploration aims to explore the sound potential of native instruments through the development of mixing, so that in the future it can be used as part of therapeutic music that can be enjoyed comfortably by its users. The research began with an exploration of bamboo flute recordings in diatonic scales. Next, a binaural beats-basedmixing experiment using an oscillator was conducted. This research produced several results of flute sound processing in the form of binaural beats in Beta, Alpha, Theta and Delta waves. The sound results were then analysed audibly and described in visual form (spectrum) and written explanation.